2020
DOI: 10.3310/hta24110
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce the risk of surgically transmitted Creutzfeldt–Jakob disease: a cost-effective modelling review

Abstract: Background Creutzfeldt–Jakob disease is a fatal neurological disease caused by abnormal infectious proteins called prions. Prions that are present on surgical instruments cannot be completely deactivated; therefore, patients who are subsequently operated on using these instruments may become infected. This can result in surgically transmitted Creutzfeldt–Jakob disease. Objective To update literature reviews, consultation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 159 publications
0
4
0
Order By: Relevance
“…5,14 The gradual but notable increase in the incidence of sCJD, but not that of genetic CJD, has also been reported in other countries with longstanding prion disease surveillance and supports the notion that it is a result of the globally ageing population. 5,16 Ascertainment mechanisms in 2021 were unchanged compared to recent years, with the majority of initial referrals coming through requests for diagnostic CSF 14-3-3 protein testing. Some proactive ascertainment mechanisms (such as state health department and tertiary hospital mortality data base searches) have ceased, while other case detection methods have increased.…”
Section: Discussionmentioning
confidence: 99%
“…5,14 The gradual but notable increase in the incidence of sCJD, but not that of genetic CJD, has also been reported in other countries with longstanding prion disease surveillance and supports the notion that it is a result of the globally ageing population. 5,16 Ascertainment mechanisms in 2021 were unchanged compared to recent years, with the majority of initial referrals coming through requests for diagnostic CSF 14-3-3 protein testing. Some proactive ascertainment mechanisms (such as state health department and tertiary hospital mortality data base searches) have ceased, while other case detection methods have increased.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this atypical set-up led to sub-optimal sensitivity. Nevertheless, our results provide evidence that, as is known to be the case for PrP prions [ 47 49 ], standard cleaning and sterilization protocols may not inactivate proteopathic seeds bound to stainless-steel.…”
Section: Resultsmentioning
confidence: 53%
“…However, the long asymptomatic incubation periods (20 years and more in some cases), the difficulties of eradicating prions from surgical instruments and the high levels of infectivity of CJD in the brain mean that there is a margin of uncertainty around quantifying the risk of iatrogenic transmission of CJD [34]. Although no studies have identified a new case over the past few years, many case reports reported a relationship between CJD and a surgical intervention [34][35][36][37]. Hence, potential CJD instrument-contamination events may continue to occur, causing widespread hospital and patient concern.…”
Section: Discussionmentioning
confidence: 99%